2018
DOI: 10.1007/s00259-018-3963-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac denervation evidenced by MIBG occurs earlier than amyloid deposits detection by diphosphonate scintigraphy in TTR mutation carriers

Abstract: In TTR mutation carriers, cardiac sympathetic denervation evidenced by decreased MIBG uptake is detected earlier than amyloid burden evidenced by DPD. These results raise the possibility of a diagnostic role for MIBG scintigraphy at an early stage of cardiac involvement in TTR-mutated carriers, in addition to its well-established prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…Although the statistics from the current study itself may have to be interpreted with caution, the results from this study are very much in line with recently reported findings in a cohort roughly twice the size of the current group. 42 and bone scintigraphy, and our results suggest that 123 I-MIBG scintigraphy seems to reflect cardiomyopathy more than cardiac neuropathy in case of heart failure, we support a more prominent role for 123 I-MIBG scintigraphy within the general work-up for newly diagnosed ATTRm amyloidosis patients. The documented important prognostic value of abnormal 123 I-MIBG results 40,43 may possibly be more related to it being a marker of ATTRm cardiomyopathy than a marker of cardiac autonomic neuropathy in case of heart failure.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Although the statistics from the current study itself may have to be interpreted with caution, the results from this study are very much in line with recently reported findings in a cohort roughly twice the size of the current group. 42 and bone scintigraphy, and our results suggest that 123 I-MIBG scintigraphy seems to reflect cardiomyopathy more than cardiac neuropathy in case of heart failure, we support a more prominent role for 123 I-MIBG scintigraphy within the general work-up for newly diagnosed ATTRm amyloidosis patients. The documented important prognostic value of abnormal 123 I-MIBG results 40,43 may possibly be more related to it being a marker of ATTRm cardiomyopathy than a marker of cardiac autonomic neuropathy in case of heart failure.…”
Section: Discussionsupporting
confidence: 75%
“…Another possibility is that prefibrillar TTR aggregates may be present already affecting the nerve function, as has been suggested in the study of Sousa et al 30 Some studies found that patients with signs of either polyneuropathy or autonomic neuropathy have higher 123 I-MIBG washout rates and lower late HMR. 28,42 The current study has some limitations. In this study, bedside maneuvers, such as the deep breathing test, Valsalva maneuver, isometric handgrip test, and heart rate and blood pressure response to standing up, were used to determine the presence of cardiac autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…CV autonomic dysfunction can present as orthostatic hypotension/intolerance, dizziness, syncope, fatigue, and blurry vision while standing [20,21,24,25], which significantly impacts patients' daily routine [20,21]. Autonomic denervation of the heart in hATTR amyloidosis [26,27] affects sympathetic and/or parasympathetic regulation, which may lead to conduction disturbances and arrhythmias [13,[28][29][30]. As these CV manifestations may also be a result of amyloid infiltration and deposition in cardiac tissue [31], the autonomic nature of these manifestations may go unrecognized.…”
Section: Introductionmentioning
confidence: 99%